Analyse ergonomique et mesures biomécaniques dans un abattoir de porcs - Patricia Richard (Perspectives Interdisciplinaires sur le Travail et la Santé)
An ergonomic study was carried out to identify working conditions with an impact on musculoskeletal disorder risk factors in a pig processing plant, and proposals for change aimed at reducing the level of risk were then made. The study took place during a workplace training period for a second cycle diploma in ergonomic intervention at the Université du Québec à Montréal. Two plant workstations were targeted, namely the carcass saw and the fat lift. Electromyography (EMG), together with a psion organizer event recorder and video, were used to observe the saw operators. Analysis of their methods revealed a muscular effort in excess of 10 % for wrist flexors when the operators kept the saw latches activated between carcasses. They did this because of cycle times and malfunctioning of the saw motor. Recommendations were made concerning the working space and the saw motor. At the fat station, working techniques and lifting effort for different types of carcasses were analyzed using a digital dynamometer and video. Recommendations were made concerning lifting techniques, working space and rotation of workers between different workstations.